Uptime strategies for excellence in maintenance management - Campbell, John Dixon; Reyes-Picknell, James V (Productivity Press, 2006)
In today's competitive marketplace, the flow of goods and services to customers must not be hindered by obstacles such as maintenance downtime. To stay on top, managers must implement strategies that keep operations performing at high levels. Uptime, 2nd Edition, is an updated and expanded version of the invaluable first edition and provides current insight into successful strategies for managers, maintenance, and non-maintenance professionals alike. Updates from the first edition include current trends in technology, reliability maintenance improvements, and the challenges of finding qualified maintenance personnel due to an aging labor force.